2012
DOI: 10.1116/1.4765088
|View full text |Cite
|
Sign up to set email alerts
|

Stable field emission of single B-doped Si tips and linear current scaling of uniform tip arrays for integrated vacuum microelectronic devices

Abstract: Articles you may be interested inEffect of ballast-resistor and field-screening on electron-emission from nanodiamond emitters fabricated on micropatterned silicon pillar arrays Enhanced electron-field emission from nanodiamond ridge-structured emission arrays capped on micropatterned silicon pillars Advanced Si-based semiconductor technology is most suitable to fabricate uniform nanostructures as integrated field emitter arrays for novel vacuum electronic devices. In order to improve the field emission homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Our fabrication approach tolerates a wide variation in the CMP step compared with the methods employing CMP for defining the gate aperture [25], [39]. In those approaches, if there are nonuniformities in the thicknesses of the gate-stack or in the planarization process, the gate aperture will not be defined uniformly across the array.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our fabrication approach tolerates a wide variation in the CMP step compared with the methods employing CMP for defining the gate aperture [25], [39]. In those approaches, if there are nonuniformities in the thicknesses of the gate-stack or in the planarization process, the gate aperture will not be defined uniformly across the array.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming R tip = 5 nm and an emitter cone angle of 30°, electric field distribution in the device was simulated by COMSOL and the emission current from the tip was estimated by integrating (1) over the tip surface for devices with different values of H tip and R ap . For larger emitter cone angles, lower electrostatic fields and emission currents are expected [25]. These simulations neglect space charge effects [26], limitation in electron supply from the Si emitter cone, and the deviation of emission current from the classical Fowler-Nordheim (FN) behavior [27].…”
Section: Device Structure and Designmentioning
confidence: 98%
“…As next step the FE properties of the extraction facets were investigated by a field emission scanning microscope (FESM) under ultra high vacuum conditions (p < 10 -7 Pa) [1] using the top contact of the LED structure as cathode and setting both contacts of the LED on the same potential. As shown in Fig.…”
Section: Characterizationmentioning
confidence: 99%
“…In [1] we demonstrated that Si-tip arrays are good candidates to fulfill the specific requirements of various integrated vacuum microelectronic device applications, e.g. sensors, due to their excellent field emission uniformity and homogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation